Supplementation of GnRH to superovulation in dairy cow improving the results of embryo production - Ty, Le Van; Phu, Huynh Xuan; Tung, Ha Thanh; Chau, Le Thi (Academia Journal of Biology, 2014)
Twenty hight productive lactate Holstein Freez sellected from the synchronized in estrous treated with PGF2α cows in Dalatmilk Farm (Da Lat, Lam Dong) were randomly divided into 2 groups for treatment of superovulation. The control group received 50AU pFSH i.m in declining dose for 5 days (from Day 8 PM to Day 12 PM, 8 injections, Day 0 was the day of estrous) with the first PGF2α at Day 11 PM. The Exp. group received at day 0 the device P4 (CIDR) for 12 days and the same dose of FSH, supplemented with two injections GnRH at day 7 and 48 hrs after the first PGF2α injections (day 11 PM). The P4 device removal was done by the last FSH injection. Embryo collection was done by 7th day after the day of the first artificial insemenation. The mean number of corpora lutea palpated (14.0±4.6 vs 10.7±3.2, P<0.05), the mean number of blastocytes (5.1±0.4 vs 3.1±1.0; P<0.01) and transferable embryos (6.8±1.8 vs 4.3±2.0; P<0.05) were higher in the group supplemented with GnRH. The interval of the first cow beginning estrous to the last one in the GnRH supplemented group was shorter compared with control group (58-64 hrs vs 50-98 hrs). So supplementation of GnRH not only improved the number of transferable embryos but also increased level of synchronization of donors